Transmembrane Na+ and Ca2+ electrochemical gradients in cardiac muscle and their relationship to force development (The Rockefeller University Press, 1982)
Na+- and CA2+-sensitive microelectrodes were used to measure intracellular Na+ and Ca2+ activities (alpha iCa) of sheep ventricular muscle and Purkinje strands to study the interrelationship between Na+ and Ca2+ electrochemical gradients (delta muNa and delta muCa) under various conditions. In ventricular muscle, alpha iNa was 6.4 +/- 1.2 mM and alpha iCa was 87 +/- 20 nM ([Ca/+] = 272 nM). A graded decrease of external Na+ activity (alpha oNa) resulted in decrease of alpha iNa, and increase of alpha iCa. There was increase of twitch tension in low- alpha oNa solutions, and occasional increase of resting tension in 40% alpha oNa. Increase of external Ca2+ (alpha oCa) resulted in increase of alpha iCa and decrease of alpha iNa. Decrease of alpha oCa resulted in decrease of alpha iCa and increase of alpha iNa. The apparent resting Na-Ca energy ratio (delta muCa/delta muNa) was between 2.43 and 2.63. When the membrane potential (Vm) was depolarized by 50 mM K+ in ventricular muscle, Vm depolarized by 50 mV, alpha iNa decreased, and alpha iCa increased, with the development of a contracture. The apparent energy coupling ratio did not change with depolarization. 5 x 10(-6) M ouabain induced a large increase in alpha iNa ad alpha iCa, accompanied by an increase in twitch and resting tension. Under the conditions we have studied, delta muNa and delta muCa appeared to be coupled and n was nearly constant at 2.5, as would be expected if the Na-Ca exchange system was able to set the steady level of alpha iCa. Tension threshold was about 230 nM alpha iCa. The magnitude of twitch tension was directly related to alpha iCa.